The Influence of Green Knowledge and Green Perceived Value on Purchase Intention Mediated by Green Lifestyle - Yulianingsih, Yulianingsih; Laela, Laela; Sardju, Himawan (International Journal of Business, Law, and Education, 2025)
This study aims to analyze the influence of green knowledge and green perceived value on purchase intention mediated by green lifestyle on Gen Z tumbler product users in Indonesia. This study was conducted through a quantitative approach with a total sample of 200. The sampling technique used was non-probability sampling with a purposive sampling approach. Data were processed using Structural Equation Modeling with the Smart Partial Least Square statistical program. The results of this study prove that: Green knowledge has no effect on purchase intention; Green knowledge has a positive effect on green lifestyle; Green perceived value has a positive effect on purchase intention; Green perceived value has a positive effect on green lifestyle; Green lifestyle has a positive effect on purchase intention; Green knowledge has a positive effect on purchase intention through green lifestyle as a mediating variable; and green perceived value has a positive effect on purchase intention through green lifestyle as a mediating variable.